Bodies in Crisis : Culture, Violence, and Women's Resistance in Neoliberal Argentina - Sutton, Barbara, 1970- (Book collections on Project MUSE., 2010)
Born and raised in Argentina, Barbara Sutton examines the complex, and often hidden, bodily worlds of diverse women in that country during a period of profound social upheaval. Based primarily on women's experiential narratives and set against the backdrop of a severe economic crisis and intensified social movement activism post-2001, Bodies in Crisis illuminates how multiple forms of injustice converge in and are contested through women's bodies and suggests that social policy, economic systems, cultural ideologies, and political resistance are ultimately fleshly matters.